Cosmos : astronomy in the new millennium - Pasachoff, Jay M; Pasachoff, Jay M; Filippenko, Alex (Cambridge, Cambridge University, 2014)
An exciting introduction to astronomy, the fourth edition of this book uses recent discoveries and stunning photography to inspire non-science majors about the Universe. Written by two highly experienced and engaging instructors, each chapter has been fully updated, with more than 200 new images throughout, including recent images from space missions and the world's best observatories. The newly redesigned text is organized as a series of stories, each presenting the history of the field, the observations made and how they fit within the process of science, our current understanding and what future observations are planned. Math is provided in boxes and easily read around, making the book suitable for courses taking either mathematical or qualitative approaches. New discussion questions encourage students to think widely about astronomy and the role science plays in our everyday lives and podcasts for each chapter aid studying and comprehension.
Appendix 561-570p.; Selected readings 571-574p.; Glossary 575-584p.; Index 585-599p.
Keywords: Astronomy; Cosmos; Physics